2014
DOI: 10.1016/j.theriogenology.2014.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Altered progesterone concentrations by hormonal manipulations before a fixed-time artificial insemination CO-Synch + CIDR program in suckled beef cows

Abstract: We hypothesized that pregnancy outcomes may be improved by inducing luteal regression, ovulation, or both (i.e., altering progesterone status) before initiating a timed AI program in suckled beef cows. This hypothesis was tested in two experiments in which cows were treated with either PGF 2 (PG) or PG + GnRH before initiating a timed AI program to increase the proportion of cows starting the program in a theoretical marginal (< 1 ng/mL; Experiment 1) or elevated (≥ 1 ng/mL; Experiment 2) progesterone environ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
1
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 27 publications
1
7
1
1
Order By: Relevance
“…The results of the present study showed no differences between treatments applied in three groups of cows to TAI (table 1). However our results (PR) of TAI in primiparous shown to be superior to Sá Filho et al (2009) and Hill et al (2014), which worked with Bos taurus indicus and Bos taurus taurus. On the other hand data from this study confirm very good results in PR when there wasclean up of the bulls for cows previously submitted to P 4 and EB in the end of the breeding season, corroborating studies of Baruselli et al (2012), which found strong increase in PR in cows pretreated with progestin and EB ( Table 1).…”
Section: Resultscontrasting
confidence: 71%
“…The results of the present study showed no differences between treatments applied in three groups of cows to TAI (table 1). However our results (PR) of TAI in primiparous shown to be superior to Sá Filho et al (2009) and Hill et al (2014), which worked with Bos taurus indicus and Bos taurus taurus. On the other hand data from this study confirm very good results in PR when there wasclean up of the bulls for cows previously submitted to P 4 and EB in the end of the breeding season, corroborating studies of Baruselli et al (2012), which found strong increase in PR in cows pretreated with progestin and EB ( Table 1).…”
Section: Resultscontrasting
confidence: 71%
“…At estrus there is also an up-regulation of several genes involved in remodeling of the extracellular matrix (Bauersachs et al 2005), and changes in transcript abundance of inhibin beta A subunit (a member of the TGF-beta signaling pathway) in the bovine intercaruncle area suggests it is involved in coordinating endometrial remodeling (Ishiwata et al 2003). The TGF-beta superfamily is known to be involved in changes in the endometrium, development of the placenta, and maintenance of the pregnancy (Jones et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…These protocols are possible since gonadotropin-releasing hormone (GnRH) is capable of inducing ovulation regardless of estrus expression or the corresponding rise in estradiol (Ryan et al 1998). However, induction of ovulation without expression of estrus has been reported to have decreased conception rates (Bridges et al 2012a;Whittier et al 2013;Hill et al 2014) likely from inadequate estrogen concentrations to properly regulate the uterine environment for subsequent sperm transport and gamete-conceptus survival Perry 2008a, 2008b). Thus, cows that did not exhibit standing estrus around the time of GnRH-induced ovulation (± 24 h) had decreased concentrations of estradiol at AI and decreased pregnancy success compared to cows that did exhibit estrus (Perry et al 2005(Perry et al , 2007Richardson et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In beef heifers, administration of PGF 2α 3 d prior to a TAI protocol increased the percentage of heifers initiating a new follicular wave and increased the synchrony of estrus after controlled internal drug release (CIDR) removal (Grant et al, 2011). Presynchronization with PGF 2α has the potential to improve follicle turnover (Perry et al, 2012;Hill et al, 2014), estrus synchrony (Grant et al, 2011), and pregnancy rates (Perry et al, 2012) in beef cattle.…”
Section: Introductionmentioning
confidence: 99%